Nurse staffing models in acute care: A descriptive study - Marianne Thériault; Carl‐Ardy Dubois; Roxane Borgès da Silva; Alexandre Prud'homme (Wiley, 2019)
Abstract Aims To identify nurse staffing groups in acute care facilities. Design This retrospective descriptive study used a configurational approach. Methods Data from a two‐month target period from January-March 2016 were collected for 40 facilities in four different hospitals in one of the largest regions of Quebec. Multiple factorial analysis and hierarchical ascendant classification were used to generate a limited number of nurse staffing groups. Results/Findings Four distinct nurse staffing groups emerged from this study. The least resourced model relied mainly on less qualified personnel and agency staff. The moderately resourced basic model was assessed as average across all staffing dimensions, but employed less overtime, relying mostly on auxiliary nurses. The moderately resourced professional group, also moderate in most variables, involved more overtime and fewer less qualified personnel. The most resourced group maximized highly qualified personnel and minimized instability in the nursing team. Conclusion This study covered multiple staffing groups with widely varying characteristics. Most groups entailed risks for quality of care at one or more levels. Few care units approached the theoretical staffing ideal.